Energy Efficient Multimedia Transmission in Wireless Sensor Networks using Enhanced Adaptive Transmission Control Algorithm and Measurement Techniques - Sumithra S; Prabhu Sandeep; Prabhakaran M; Prabu R Thandaiah (Measurement Science Review)
Wireless multimedia sensor networks (WMSNs) face challenges such as high energy consumption, latency, and ensuring secure data transmission, especially for real-time multimedia applications. To address these issues, this study proposes the enhanced adaptive transmission control algorithm (EATCA), which integrates a bidirectional long short-term memory (LSTM) model and chaos-based lightweight cryptography. EATCA optimizes energy consumption, reduces latency, and improves data security through the use of adaptive clustering and predictive transmission techniques. The algorithm uses meta-heuristic optimization for cluster head selection and fuzzy logic for route prioritization to ensure efficient data transmission. A chaos-based encryption scheme ensures data confidentiality with minimal computational overhead. The simulation results show that EATCA achieves 43.53 % lower energy consumption compared to traditional low energy adaptive cluster hierarchy (LEACH) protocols, a 96 % packet delivery ratio (PDR), and a 42 ms latency, making it suitable for time-sensitive multimedia applications. The system also achieves an 85 % compression ratio while maintaining security overhead as low as 7 %. These results make EATCA a reliable and energy-efficient solution for optimizing WMSNs and pave the way for scalable and secure network implementations.